Implementing a Cooperative E-Learning Model by Virtual Interviews with Native Speakers - Febrianti Nurul Hidayah (Teknodika, 2021)
This study aimed to define the impact of the cooperative learning model through virtual interviews with native speakers on learning outcomes and student perceptions in English course. This strategy is applied to overcome obstacles in the absence of offline learning (face-to-face in class) during the covid-19 pandemic; thus, online learning methods need to be modified to optimize student ability in English. A total of 135 students were given a questionnaire to determine their opinion about the virtual interviews and their learning progress. Half of the students taught through the virtual interview with native speakers (experimental group) and the others without native speakers (control group). Results showed that both groups showing increases in speaking confidence and their perception of the learning process, but the experimental group’s mean percentage was higher than in the control group. Therefore, the cooperative learning model's implementation can lead to positive outcomes since they could engage students in the English learning process. The implication of this study calls for the cooperative learning model implementation did not only make students active and motivated in learning, but also can improve the effectiveness and quality of learning.